Addiction Social Work Fellowship Program in Canada. Issue 3 (3rd July 2018) - Callon, Cody; Bosma, Harvey; Klimas, Jan
Abstract : Substance use disorders (SUD) disproportionally contribute to the global social and economic cost of disease; however, their treatment has been inadequate in large part due to an enduring research to practice gap in which competencies for treating and preventing SUDs are often lacking from social work education curricula. Training social workers in managing SUDs has been separated from nurse and physician training, partly due to the long-standing divide between the behavioral health and medical care system. Recently, a new interdisciplinary fellowship in addiction social work, nursing and medicine has been established in Vancouver, Canada. We describe the novel fellowship program and outline initial impact of the training on knowledge and skills in addiction social work from our qualitative evaluation of the fellowship. We conclude that training social workers, and other allied health professionals alongside physicians and nurses may extend the reach of this type of training program even further.